Diagnosis and treatment of a rare bilateral primary thyroid cancer: a case report - Lin, Hai; Zhang, Xinyu; Yan, Na; Guo, Tao; Chen, Qiu; Huang, Xianen; Wang, Dandan; Wu, Weili (Frontiers in Oncology, 2025)
Preoperative ultrasound examination of thyroid nodules is the most economical and effective screening method for diagnosing thyroid nodules. Fine-needle aspiration biopsy (FNAB) cytology guided by ultrasound has high sensitivity and specificity in distinguishing benign and malignant thyroid nodules. However, approximately 25% of thyroid nodules cannot be determined by FNAB, and accurate differentiation of benign and malignant thyroid nodules is critical for patient prognosis. Here, we report the diagnosis and surgical treatment process of a rare patient with bilateral thyroid malignant tumor of independent origin. This patient had significantly elevated levels of calcitonin (Ctn: 130.00 pg/mL) and carcinoembryonic antigen (CEA: 16.13 ng/mL). Ultrasound shows a solid nodule on the left side of the thyroid gland, measuring 1.2*0.8*0.9cm, TI-RADS 4A; right solid nodule, 1.3*0.7*0.9 cm, TI-RADS 3. A fine needle biopsy of the left nodule showed little glandular epithelium and no evidence of malignancy. Multi-gene joint analysis of RET C634R in the left nodule and BRAF V600E in the right nodule indicated a potential diagnosis of left medullary thyroid carcinoma (MTC) and right papillary thyroid carcinoma (PTC). Postoperative pathology revealed the left thyroid nodule was MTC and the right nodule was PTC. The patient’s bilateral thyroid nodules are independent primary malignant lesions. This case emphasizes the important significance of combined analysis of ultrasound, serum biomarkers, cellular pathology, molecular detection, and paraffin pathology in the differential diagnosis of benign and malignant multiple thyroid nodules. It provides a reference for future diagnosis and treatment decisions of multiple thyroid nodules.